The National Identity of Arab Parents Whose Children are Being Treated in Israeli Hospitals in the Center of the Country - Badir, Rodayna Kamal; Nassralah, Omar Abd-Elraheem (Journal of Humanities & Social Sciences, 2022)
This research aims to identify the extent of interaction and the shared experience among the parents inside the hospital in enhancing and strengthening the Israeli identity of the parents of Arab children who receive treatment inside the hospital. This research included two groups: the research group - 62 Arab parents whose children were hospitalized for treatment, and the examination group - 32 Arab parents who did not have children in the hospital. Data were collected by means of a form that was filled out at the beginning and end of hospital treatment, and by the comparison group filled out at the same times as the comparison group. The results of the research indicated a clear difference in the strengthening of the Israeli identity among the families of the children who stayed for treatment in the Israeli hospitals, and in return there was a decrease in sympathy with the Palestinian Arab identity compared to the parents of their children who did not stay in the hospital. It also showed that the duration of hospitalization has importance and impact on strengthening the Israeli identity. The results of the research also indicated the relationship of families with the satisfaction of receiving treatment in the Israeli hospital in favor of strengthening the Israeli identity. It was noted according to the results, in contrast with the compared groups, that there was a significant increase in the Israeli identity and a decrease in the Arab identity, as well as the length of stay in the hospital and the extent of parents’ satisfaction with the stay (hospital setting experience) were important reasons for this increase. The research contribution emphasizes the inherent importance of educational dialogue, as well as the need to understand the special needs of each group of parents, and indicates the importance of joint work in increasing the common identity of minorities.